Sedimentary evolution and tectonic setting of the Itapucumi Group, Ediacaran, northern Paraguay: From Rodinia break-up to West Gondwana amalgamation - Warren, L. V. [UNESP] (2019)
The Itapucumi Group is recognized worldwide due to its well-preserved Ediacaran fossil assemblage. Despite its paleontological importance, this unit remains as the least studied South American Neoproterozoic sedimentary succession. Recorded at northern Paraguay, the Itapucumi Group is a similar to 400 m-thick siliciclastic and carbonate succession deposited on the Paleoproterozoic basement of the Rio Apa Craton. At west, this unit is deformed and metamorphosed, whereas the eastern domain constitutes an undeformed cratonic cover. The Itapucumi Group comprises, from base to top, siliciclastic rocks of the Vallemi Formation, succeeded by limestones and dolomites of the Camba Jhopo and Tagatiya Guazu formations, which are capped by marls and mudstones of the Cerro Curuzu Formation. The entire sedimentary succession consists of three depositional sequences deposited in a large rimmed carbonate platform open to the ocean westward: S.1, the lowermost predominantly terrigenous, and sequences S.2 and S.3, comprising carbonate and terrigenous facies associations. Carbon isotope data from limestones and dolostones show values of + 1.93 parts per thousand delta C-13 VPDB and Sr-87/Sr-86 ratios of 0.7084 and 0.7089, in agreement with a depositional age between 600 Ma and 550 Ma and coherent with the Cloudina biozone. These data support the paleogeographic correlation between the Itapucumi and Corumba groups at the margins of the Amazonian and Rio Apa Craton. The siliciclastic basal successions of both units, are interpreted as deposited in rift basins developed during the fragmentation of the Rodinia supercontinent (Cryogenian to Ediacaran). Later thermal subsidence led to the generation of a new accommodation space around 550 and 528 Ma, recording extensive carbonate platforms along the margins of Pampia, Amazonian and Rio Apa cratons. The deformation of the Itapucumi and Corumba basins started at around 528 Ma, and was controlled by the reactivation of listric and normal faults generated during the rift stage. The opposite tectonic vergence observed in the Vallemi and Paraguay fold-and-thrust belts can be ascribed to oppose master fault polarities in the precursor basins of this context, as well as to the rigid behavior of the Rio Apa Craton. The compressional phase ended around 484 Ma, and corresponding to the last stresses related to the Brasiliano Cycle and the closure of SW Gondwana.